O-011 Prevalence and outcomes of unruptured intracranial aneurysms in the trauma population. (23rd July 2022) - Nguyen, V; Schwartz, B; Barats, M; Motiwala, M; Himel, S; Elijovich, L; Inoa, V; Goyal, N; Khan, N; Hoit, D; Arthur, A; Nickele, C
Abstract : Background: Much of the data on the prevalence of unruptured intracranial aneurysms (UIAs) varies significantly by study modality and suffers from under or overestimation due to selection bias or methodological flaws. 3 Autopsy studies have shown rates ranging from 0.2–9% 5 and angiographic studies have demonstrated rates ranging from 1–5%. 2 Non-invasive imaging studies have shown UIA rates ranging from 1.4–8.4%. 1 When different methodologies show UIA prevalence rates that vary by a factor of 5 or more, it is reasonable to conclude that certain techniques are yielding erroneous prevalence rates. Although some prior studies have attempted to address this statistically, this may not be possible. 3, 4 This study aimed to determine the incidental aneurysm prevalence in the trauma population. We hypothesize that although the trauma population may be younger than the general population, it may be more representative of the general population and therefore yield a more accurate estimate of aneurysm prevalence. Methods: We performed a retrospective review of patients in a prospectively maintained trauma database at a Level 1 Trauma Center from 2019–2020. CT angiograms with radiology reads were assessed for the presence of an intracranial aneurysm. Demographic and follow-up data were collected from patients who were found to have an intracranial aneurysm. Results: 5978 out of 8999 patients (66.4%) had CTA studies performed. The average age of a patient with a CTA performed was 44.6 years. 54 patients with aneurysms were identified for an overall rate of 0.90%. The average age of a patient with an aneurysm was 64.2 years. The highest aneurysm rate per age group was 3.13% in 80 to -89-year-olds. The aneurysm rate was 1.04% in females and 0.83% in males. African Americans had the lowest rate of aneurysms at 0.77%, while Asians were the highest at 6.67%. 74.1% of aneurysms were anterior circulation (average largest diameter 3.4 mm), 13.8% posterior circulation (4.4 mm), and 12.1% cavernous (3.3 mm). 75.9% of patients with aneurysms did not follow up at the trauma center, 1.85% (one ACOMAcomm) was ruptured and treated with coiling, 9.26% died due to traumatic injuries or other reasons unrelated to aneurysmal rupture, and 12.96% were followed up conservatively with outpatient imaging. Conclusions: The aneurysm prevalence rate in the trauma population is lower than that described in many previous UIA prevalence studies. This population may be more representative of the general population than what has been used in prior studies. Further, compared to angiography and autopsy, CTA is a more pragmatic way to assess for incidental aneurysm prevalence given that the majority of UIAs are found on CTA or MRA – which is a substantially similar technology. This has significant ramifications for the treatment of unruptured intracranial aneurysms. Disclosures: V. Nguyen: None. B. Schwartz: None. M. Barats: None. M. Motiwala: None. S. Himel: None. L. Elijovich: None. V. Inoa: None. N. Goyal: None. N. Khan: None. D. Hoit: None. A. Arthur: None. C. Nickele: None.